DEVELOPMENT OF DIGITAL COMICS WITH SPIRITUAL VALUES AS A LEARNING MEDIA FOR CHEMICAL BONDING TOPIC IN CLASS X HIGH SCHOOL - Denada Septiani Yesa; Ayi Darmana; Andini Zahra (Universitas Negeri Surabaya, 2026)
Chemical bonding is a fundamental topic in chemistry that students often find difficult to understand because the concepts are abstract and require strong visualization skills. Therefore, innovative learning media are needed to support students’ conceptual understanding and increase their engagement in the learning process. This study aims to develop digital comic learning media integrated with spiritual values for chemical bonding material that meets the criteria of validity, practicality, and student responses. This research employed the Research and Development (R&D) method using the 4D development model consisting of define, design, develop, and disseminate stages; however, this study was limited to the develop stage. Data were collected through needs analysis questionnaires, expert validation sheets, teacher practicality assessment questionnaires, and student response questionnaires. The validation procedure included chemistry content specialists, learning media experts, and spiritual value integration experts. A small study was carried out with tenth-grade pupils at a senior high school. The findings indicated that the designed digital comic media met the feasibility criteria. The validation results yielded an average Aiken's V value of 0.89, which is classified as very valid. The practicality assessment by the chemistry teacher provided an average score of 3.65 out of 4.00, suggesting a very practical area. Student responses also indicated positive results with an average percentage of 78.65%. This study contributes to chemistry education by providing an innovative digital comic learning media integrated with spiritual values that supports students’ understanding of abstract chemical bonding concepts.